The Comparison of Time Management and Learning Motivation on Academic Achievement of Students at SMA Negeri 1 Koto Besar - Aprilla, Yeni; Arsis , Asi Noflanda; Andre , Lesis; Yunanda , B.R.E. (The Future of Education Journal, 2025)
The background of this study is that the main goal of students is essentially to learn and develop their thinking patterns. To achieve this goal, students must engage in various learning activities to attain good academic performance and complete their learning process on time. However, many students face difficulties in time management, which leads to neglecting assignments and tasks. Given these issues, time management and learning motivation are key factors in student success during the learning process and in improving academic performance. This research uses a descriptive quantitative approach, with data collection techniques through questionnaires distributed to 33 respondents using non-probability sampling, from a total population of 83 people. The data was measured using a Likert scale. The indicators used in this study are study time planning, goal setting, prioritization and scheduling, interest in learning, motivation, aspirations, and the desire to achieve better performance. The study also employs multiple linear regression analysis, classical assumption testing, and hypothesis testing with data processing using SPSS 21, presented descriptively. Based on the results of the comparison between time management, learning motivation, and academic performance of students at SMA Negeri 1 Koto Besar, the data analysis indicates that from the ANOVA test, if time management is improved by 1%, academic performance will increase by 25%, and if learning motivation is increased by 1%, academic performance will improve by 15%. This is reinforced by an R-squared value of 0.801. This indicates that there is a strong relationship between time management, learning motivation, and academic performance at SMA Negeri 1 Koto Besar, accounting for 80% of the variance, while 20% is influenced by other factors not examined in this study.